The Relevance of Jamal Al-Banna's Islamic Legal Thoughts with Religious Moderation in Indonesia - Lubis, Sakban; Ependi, Rustam; Tumiran, Tumiran; Harahap, Muhammad Yunan; Hakim, Abdul (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This research aims to find out the relevance of Jamal Al-Banna's Islamic Legal Thought with Religious Moderation in Indonesia. This research is a doctrinal Islamic legal research using historical approach method (content analysis). The primary data source of this research is Jamal al-Banna's own work, namely Nahwa Fiqh JadÃ®d and the book Religious Moderation written by the Balitbang Team of the Indonesian Ministry of Religion. This research is also supported by secondary sources in the form of works related to the topic of study. The result of this research is that the Relevance of Jamal Al-Banna's Islamic Legal Thought with Religious Moderation in Indonesia. textually there are 2 (two), namely: justice and tolerance. As for substantially there are also 2 (two), namely: the value of the principle of "convenience" is the same as tawassuá¹ and compassion is the same as the principle of equality (musawah/egalitarian).